2020
DOI: 10.1021/acsphotonics.9b01727
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Semiconductor–Metal ε-Ga2O3 Solar-Blind Photodetectors with a Record-High Responsivity Rejection Ratio and Their Gain Mechanism

Abstract: In recent years, Ga2O3 solar-blind photodetectors (SBPDs) have received great attention for their potential applications in solar-blind imaging, deep space exploration, confidential space communication, etc. In this work, we demonstrated an ultra-high-performance ε-Ga2O3 metal–semiconductor–metal (MSM) SBPD. The fabricated photodetectors exhibited a record-high responsivity and fast decay time of 230 A/W and 24 ms, respectively, compared with MSM-structured Ga2O3 photodetectors reported to date. Additionally, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
98
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 177 publications
(112 citation statements)
references
References 66 publications
(113 reference statements)
0
98
0
2
Order By: Relevance
“…PD-SL-NSs possesses a superior specific detectivity of 1.58 Â 10 13 Jones and a higher LDR of 51 dB, indicating that PD-SL-NSs has the strong ability to acquire high signal to noise ratio. [19] Meanwhile, as for self-powered mode, i.e., under zero bias, it exhibits a relatively high detectivity of 1.17 Â 10 12 Jones and a higher LDR of 46 dB. Table 1 compares the performance parameters of the photodetectors.…”
Section: Resultsmentioning
confidence: 99%
“…PD-SL-NSs possesses a superior specific detectivity of 1.58 Â 10 13 Jones and a higher LDR of 51 dB, indicating that PD-SL-NSs has the strong ability to acquire high signal to noise ratio. [19] Meanwhile, as for self-powered mode, i.e., under zero bias, it exhibits a relatively high detectivity of 1.17 Â 10 12 Jones and a higher LDR of 46 dB. Table 1 compares the performance parameters of the photodetectors.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, this strongly illustrates that defects or interface states within the film and the M-S barrier play a crucial role in determining the current transport mechanism. [25][26][27][28] Current and voltage show strong dependence on the further increase in the voltage (>65 V). It shows that a new gain mechanism has played a role under high bias.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, this strongly illustrates that defects or interface states within the film and the M–S barrier play a crucial role in determining the current transport mechanism. [ 25–28 ]…”
Section: Resultsmentioning
confidence: 99%
“…found that using ε‐Ga 2 O 3 , the gain of MSM‐PDs could reach 1150; meanwhile, the response speed was not too slow (24 ms). [ 136 ]…”
Section: Research Status Of Msm‐pdsmentioning
confidence: 99%